(untitled) - Sollenberger, Harold M. (Cincinnati, Ohio, 1996)
This text merges ideas from production and service activities, computer-based information systems, quality management, cost management, global business, and ethics, into proven techniques and tools basic to business decision making
Keywords: Managerial accounting,Kế toán quản trị